2006
DOI: 10.1002/chem.200501600
|View full text |Cite
|
Sign up to set email alerts
|

Catecholase Activity of a Copper(II) Complex with a Macrocyclic Ligand: Unraveling Catalytic Mechanisms

Abstract: We report the structure, properties and a mechanism for the catecholase activity of a tetranuclear carbonato-bridged copper(II) cluster with the macrocyclic ligand [22]pr4pz (9,22-dipropyl-1,4,9,14,17,22,27,28,29, 30-decaazapentacyclo[22.2.1.1 4,7 .1 11,14 . 1 17,20 ]triacontane-5,7(28), 11(29),12,18, 20(30),24(27),25-octaene). In this complex, two copper ions within a macrocyclic unit are bridged by a carbonate anion, which further connects two macrocyclic units together. Magnetic susceptibility studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…S11, S12), which is in agreement with many other catecholase model systems. [69][70][71][72] According to the MichaelisMenten model, the observed pseudo-second order reaction rate constant (k', slope of the lines in Figure S11) Figure S11), which confirms the validity of our kinetic data. pH-dependent absorption spectra of Cu(II)-L 1 -H 2 4NC ternary systems were followed at different complex-to-H 2 4NC ratios ( Fig.…”
Section: Tablesupporting
confidence: 73%
See 1 more Smart Citation
“…S11, S12), which is in agreement with many other catecholase model systems. [69][70][71][72] According to the MichaelisMenten model, the observed pseudo-second order reaction rate constant (k', slope of the lines in Figure S11) Figure S11), which confirms the validity of our kinetic data. pH-dependent absorption spectra of Cu(II)-L 1 -H 2 4NC ternary systems were followed at different complex-to-H 2 4NC ratios ( Fig.…”
Section: Tablesupporting
confidence: 73%
“…Catechol oxidases are type 3 copper enzymes, 66,67 therefore mostly dinuclear complexes were used for the biomimetic studies. [68][69][70][71][72][73][74] Nevertheless, several mononuclear [75][76][77] or trinuclear 78 complexes were also reported to possess important catecholase-like activity. To screen the enzyme mimetic properties of our oligonuclear copper(II) complexes, their catecholase activity was investigated by using the widely studied 3,5-di-tert-butylcatechol (H 2 DTBC) as model substrate.…”
Section: Oxidation Of 35-di-tert-butylcatechol: Kinetic Studymentioning
confidence: 99%
“…Design and study of model complexes for catechol oxidase and other type 3 copper centers has been an area of much interest [6][7][8][9][10] and various nitrogen-containing binucleating ligands have been used to generate dicopper complexes [6,[15][16][17][18]. 2,6-Bis[bis(pyridin-2-ylmethylamino)methyl]-4-methylphenol (H-BPMP), employed previously to model catechol oxidase [19,20], provides a nitrogen-rich coordination set similar to that of the enzyme (three nitrogen donors) and has previously furnished both trigonal bipyramidal and square pyramidal geometries.…”
Section: Introductionmentioning
confidence: 99%
“…3, the band at 400 nm increased in intensity with the reaction time at room temperature, indicative of the formation of 3,5-DTBQ and the successive increment of its concentration. Simultaneously the band at 625 nm decreased in intensity with time, indicating that the Cu 21 In all investigations, it was found that the catalytic reaction was finished after 1 h, indicative of the much lower activity of our employed dicopper complexes on comparison with the reported dicopper complexes earlier, 6,20 their catalytic oxidation being generally finished within a few minutes at low catechol to complexes ratios. The reason for this observation can be tentatively ascribed to the stereo effects of the ligands we employed in this work, and our initial investigations on the catalytic activity of the complex [Cu 2 (pmpzpo) 2 ]Br 2 ·CH 3 OH, with more bulky substituents at the 3-position of the pyrazolyl rings, strengthened this assumption.…”
Section: Catechol Oxidase Model Studiesmentioning
confidence: 73%